Comparative Analysis of Enzymatic and Immunological Biosensors in Biomedical Applications - Saxena Abhishek; Praveena K.; Manjunatha; Kalbande Vijay; Khan Irfan; Maan Preeti; Zabibah Rahman S. (E3S Web of Conferences, 2024)
Biosensors are essential for transforming biological signals into electrical ones and have a wide range of uses in the biomedical, agricultural, and environmental fields. A biosensor is a device that combines biological and physicochemical elements to detect changes in physiological or biochemical states. This paper provides a comprehensive overview of the development and application of enzymatic and immunological biosensors, emphasizing their significant role in environmental, agricultural, and biomedical sectors. By leveraging the unique properties of natural polysaccharides, particularly cellulose, for their construction, these biosensors offer enhanced biocompatibility, robust mechanical strength, and costeffectiveness. This study discusses the principles underlying biosensors, including their biological recognition elements, transduction mechanisms, and output systems. Enzymatic biosensors, characterized by their use of enzymes as bio receptors, and immunological biosensors, utilizing antibodies or antigens for the detection of immunocomplex formation, are evaluated in detail. Through comparative analysis, the paper highlights the diverse functionalities, sensitivities, and applications of these biosensors, ranging from glucose and hydrogen peroxide detection to monitoring of protein markers and E. coli bacteria. The study underscores the biosensors’ ability for facilitating rapid, incredibly sensitive, and specific detection capabilities, critical for advancing scientific diagnostics, environmental surveillance, and food protection.